Ergonomic usability evaluation and inclusive redesign of diagnostic imaging device interfaces for aging sonographers - Hokyoung, Lee (Edelweiss Applied Science and Technology, 2025)
With the increasing age of healthcare professionals, the number of older sonographers in the workforce is on the rise. Despite this, limited research addresses the specific usability challenges of ultrasound device interfaces for this demographic. This study aims to identify and address usability issues in diagnostic imaging devices to enhance their user experience for aging sonographers. A usability evaluation framework was established, focusing on task workflow, interface design, and risk prevention. Fifteen evaluation criteria were developed based on recognized design principles, and a workflow encompassing ’Patient,’ ’Scan,’ ’Measurement,’ and ’End Exam’ was designed in collaboration with clinical experts. Usability tests were conducted with participants who subsequently provided feedback through interviews. Thematic analysis of the interview data was performed using NVivo, with survey responses complementing the findings. Interviews highlighted recurring themes, including automation-related functions within the ’Task Process’, overly complex screens with dense button layouts in ’Interface Design’, and the need to safeguard patient data from accidental deletion under ’Errors and Risk Factors’. Additionally, survey data revealed that the ‘Patient’ and ‘Scan’ stages elicited the most feedback, with concerns focusing on button and text readability, as well as a desire for a ‘Back’ button. Older sonographers face unique ergonomic and usability challenges, including visual fatigue and upper extremity discomfort. Addressing these issues through improved interface design—emphasizing readability, simplicity, and error prevention—can enhance safety and efficiency. The findings offer actionable insights for designing medical devices tailored to aging healthcare professionals.